2012
DOI: 10.1371/journal.pone.0046648
|View full text |Cite
|
Sign up to set email alerts
|

Opsonic and Protective Properties of Antibodies Raised to Conjugate Vaccines Targeting Six Staphylococcus aureus Antigens

Abstract: Staphylococcus aureus is a major cause of nosocomial and community-acquired infections for which a vaccine is greatly desired. Antigens found on the S. aureus outer surface include the capsular polysaccharides (CP) of serotype 5 (CP5) or 8 (CP8) and/or a second antigen, a β-(1→6)-polymer of N-acetyl-D-glucosamine (PNAG). Antibodies specific for either CP or PNAG antigens have excellent in vitro opsonic killing activity (OPKA), but when mixed together have potent interference in OPKA and murine protection. To a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 68 publications
(122 reference statements)
1
47
0
Order By: Relevance
“…S. aureus also has a wide spectrum of virulence factors and disease types, and as such, a single vaccine may not protect against the broad range of staphylococcal infections. Efforts to create multicomponent vaccines and to induce both cellular and humoral immune responses are under way by several groups (40)(41)(42), and these multivalent vaccines often include CP antigens. Despite the failure in clinical trials of CP5 and CP8 conjugate vaccines, staphylococcal CPs are still important vaccine targets, since they are expressed in 70 to 80% of S. aureus clinical isolates and are essential for bacterial survival in blood (6).…”
Section: Figmentioning
confidence: 99%
“…S. aureus also has a wide spectrum of virulence factors and disease types, and as such, a single vaccine may not protect against the broad range of staphylococcal infections. Efforts to create multicomponent vaccines and to induce both cellular and humoral immune responses are under way by several groups (40)(41)(42), and these multivalent vaccines often include CP antigens. Despite the failure in clinical trials of CP5 and CP8 conjugate vaccines, staphylococcal CPs are still important vaccine targets, since they are expressed in 70 to 80% of S. aureus clinical isolates and are essential for bacterial survival in blood (6).…”
Section: Figmentioning
confidence: 99%
“…In addition, we believe that virulence determinants that are found to strongly impact colonization and virulence phenotypes in MRSA strains with considerable epidemiological importance, wide geographical distribution, and likely further spread, such as SasX, should also be analyzed as potential vaccine targets. Other surface proteins, such as ClfA or IsdA, which impact nasal colonization in animal models, have previously shown success as immunogens in experimental animal colonization studies (22)(23)(24). For these reasons, we here analyzed whether active and passive immunization with SasX as the target reduces S. aureus skin and lung infection and has the potential to reduce S. aureus nasal colonization.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several proteomic studies have been reported and this improved our understanding of staphylococcal cell physiology, virulence, and associated host responses (9,13,29,30). However, most of these studies were carried out with a single strain or infection type with limited follow-up using data on patient serum antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…The exoproteins Hla, IsdB, IsaA, and ClfA elicit significantly higher levels of antibodies in patients than in healthy carriers. Such immunogens play key roles in host protection by enhancing opsonic activity and inducing cytokine and chemokine production to promote immune cell recruitment (12,13). Unfortunately, the efficacy of these protective actions has not been transformed into a licensed vaccine, underscoring the need for a better understanding of host responses to the different types of infection caused by S. aureus.…”
mentioning
confidence: 99%